(untitled) (Bangladesh Journal of Medical Physics, 2017)
Tetrapolar Impedance Measurement (TPIM) is a 4-electrode impedance measurement system appropriate for a volume conductor in which current is driven through a pair of electrodes while potential developed across another pair of electrodes is measured to provide a value of transfer impedance. The 8-electrode Focused Impedance Method (FIM-8) consists of two concentric and orthogonal linear TPIM systems with their transfer impedances added for the purpose of localizing the central zone. Detailed 3D sensitivity studies are necessary for proper application of the techniques in specific biomedical applications and most reported work present point sensitivity distributions. The present work mainly focuses on planar average sensitivity in planes parallel to the electrode plane and its variation with depth due to different combinations of electrode separations both for current drive pair and the potential measuring pair. This was obtained through finite element simulation using COMSOL Multiphysics software for a 40x40x40cm3 volume. The results give useful information that can be used to design electrode configurations and measurement modalities for various applications. Bangladesh Journal of Medical Physics Vol.8 No.1 2015 22-31